Quantification of total phenolic compounds in papaya (carica papaya) peels - Jamal, Parveen; Akbar, Iqrah; Jaswir, Irwandi; Hashim, Yumi Zuhanis Has-Yun (Universiti Putra Malaysia, 2016)
Phenolics are widely distributed in many plants and are known to play a major role in the plant and animal kingdom. Phenolics exhibit strong antioxidant properties and have been used as antitumor, anticarcinogenic, antiviral and hypotensive agents. Plant by products contain a variety of these phenolic compounds and can therefore be used as an alternative source due to their higher antioxidant capacity and low toxicity compared to those of synthetically derived phenolics. In this study, ‘Sekaki’ papaya (Carica papaya) peels were used as an alternative source of phenolics and Response Surface Methodolgy (RSM) was employed to optimize the process conditions to achieve the highest phenolic content from the fruit peels. Total Phenolic Content was analyzed using Folin-Ciocalteau's method and the total phenolic content (TPC) was expressed as Gallic Acid Equivalent (GAE). The highest TPC i.e 1735.1 mg/L GAE was obtained at a temperature 1200C, time of 5 hours in a solid-solvent ratio of 1:40 g/mL while the lowest TPC of 616.57 mg/L GAE at temperature of 900C, 3 hours’ time period at a solid-solvent ratio of 1:20 g/mL. With such a high phenolic content, ‘Sekaki’ papaya (Carica papaya) peels can be used as a natural antioxidant and can protect the human body against various free radical associated diseases.